Metalinguistic Knowledge/Awareness/Ability in Cognitive Translation Studies: Some Questions - Halverson, Sandra L. (HERMES - Journal of Language and Communication in Business, 2018)
Throughout the history of contemporary Translation Studies, theoretical, empirical and pedagogically oriented work has made use of a range of notions that assume a translator’s metalinguistic knowledge, or knowledge about language, rather than knowledge of a language or languages. Examples include ideas such as ‘translation strategies’, translational ‘problem-solving’, ‘the monitor model’ and models of translator competence. Issues related to learning, automatization, and consciousness also figure in many of the discussions. At the same time, studies in bi- and multilingualism and second (and third) language acquisition have also developed a range of related ideas and concepts to deal with some of the same issues and concerns in bi- and multilingual language production more broadly (see e.g. Jessner 2006: 40-43). Some recent translation process studies have begun to target questions related to metalinguistic awareness (e.g. Ehrensberger-Dow/Künzli 2010, Ehrensberger-Dow/Perrin 2009) while the underlying assumptions of some of the commonly used ideas are also being questioned (e.g. Muñoz Martín 2016a). The range of available ideas, the significant differences between them, and the increasingly important role these ideas are playing in cognitive translation research mandate a critical look at this conceptual field. In this paper, I present some current views on metalinguistic knowledge/awareness/ability within the bi- and multilingualism and second language acquisition (SLA) literature, and compare these to some of the most widely used constructs in Cognitive Translation Studies (CTS). The aim is to clear the conceptual ground and to single out some of the most pressing questions to be addressed regarding this particular aspect of translational cognition.